Management of Thirst in Hemodialysis Patients in Primary Services - Sri Lestari; Iri Kuswadi; Heru Prasanto (Faculty of Medicine, Public Health, and Nursing, 2021)
The incidence and prevalence of chronic kidney disease (CKD) has increased worldwide and in Indonesia. There were about 53,940 people with stage 5 CKD based on data from the Indonesian Renal Registry (IRR) in 2018. Incidence crude rate is 251 per million population and prevalence crude rate is 499 per million population for the entire population1. The prevalence of CKD has almost doubled in 5 years, from 2‰ in 2013 to 3.8‰ in 2018. Hemodialysis (HD) is a renal replacement therapy modality that is in great demand by the public compared to the other two modalities, namely peritoneal dialysis and kidney grafts. In 2018, there was a consistent increase in the number of new patients and active HD patients. Active patients is the total number of patients (either new or old patients) who are still undergoing routine HD. The number of new patients has doubled compared to 2017. This also resulted in a sharp increase in the number of active patients compared to the previous year.